Nuclear and Related Techniques for Enhancing Livestock And Agriculture Productivity - Khanal, D. R.; Munankarmy, R. C. (Journal of Agriculture and Environment, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Uses of isotopes and nuclear related techniques in livestock and agriculture are discussed in this review. How developed countries are using (125I) in radioimmunoassay (RIA) of progesterone hormone in serum/milk of cattle to optimize reproductive efficiency is briefly described. In addition, this paper discusses about the uses of (15N) in soil to know the dynamics of nitrogen and uses of Hydro Probe to determine moisture content in the soil. This review will also shed some light on the potential uses of isotopes and nuclear techniques and the necessity of such technology in Nepal for improving overall agricultural productivity. Key words: Radioimmunoassay; Progesterone; Productivity; Reproductive efficiency The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 150-155